PENGARUH KUALITAS PRODUK DAN KUALITAS PELAYANAN TERHADAP LOYALITAS PELANGGAN MELALUI KEPUASAN PELANGGAN - Dwi Putri Handayani; Saryadi Saryadi; Sendhang Nurseto (Jurnal Ilmu Administrasi Bisnis, 2013)
Rabbani Pandanaran Muslim Boutique Semarang is one area of ​​business that offers products such as the veil, Muslim clothing, and the like, both for women and adam. As a company engaged in the marketing of the product, the quality of products and services becomes important. The research is motivated by data last months of customer Rabbani Muslim Boutique Pandanaran fluctuated Semarang (changing) and have not reached the target number of customers steadily. This study aims to determine the effect of service quality and customer loyalty tehadap locations through customer satisfaction. The results showed that the total effect of product quality and service quality on customer loyalty through customer satisfaction by 24.5 percent